Penerapan Model Pembelajaran Inquiry Lesson Untuk Meningkatkan Penguasaan Konsep Hukum Newton Pada Siswa Kelas VIII SMP Negeri 71 Maluku Tengah - Laisina, Christovel Johandry; Huliselan, Estevanus Kristian; Tamaela, Elsina Sarah (Physikos: Journal of Physics and Physics Education, 2023)
This study uses the Inquiry Lesson learning model to determine the improvement of mastery of Newton's Law concept in 20 students at SMP Negeri 71 Central Maluku. This research is quantitative descriptive research with a pretest-posttest design. Analysis of the acquisition of learning outcomes based on the initial test score, which indicates the mastery of the initial concept, and the final test, which indicates the mastery of the final concept, as well as the improvement of learning outcomes using the average normalized gain (N-Gain). The initial test results showed that all students (100%) were in the failing qualification with the lowest score of 13.25, the highest score of 22.00, and the average mastery of the material of 13.47. This situation shows that all students need initial abilities related to Newton's law. After applying the Inquiry Lesson learning model, the impact students have completely mastered Newton's Law with an average final test score of 78.33, where the lowest score is 72.05 and the highest score is 97.05. Based on the analysis of the increase in concept mastery using N-Gain, the average increase is 0.81, included in the high category. The results of this study indicate that the Inquiry Lesson learning model can improve students' mastery of concepts, especially Newton's Law.